2022
DOI: 10.3390/s22134910
|View full text |Cite
|
Sign up to set email alerts
|

Kinect-Based Assessment of Lower Limbs during Gait in Post-Stroke Hemiplegic Patients: A Narrative Review

Abstract: The aim of this review was to present an overview of the state of the art in the use of the Microsoft Kinect camera to assess gait in post-stroke individuals through an analysis of the available literature. In recent years, several studies have explored the potentiality, accuracy, and effectiveness of this 3D optical sensor as an easy-to-use and non-invasive clinical measurement tool for the assessment of gait parameters in several pathologies. Focusing on stroke individuals, some of the available studies aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…The IR camera can have a resolution of 1 MP 1024 × 1024 pixels. It has been successfully used and validated in human gait analysis [ 52 , 53 , 54 ]. The RGB-D sensor system can estimate features of gait patterns in pathological individuals and differences between disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR camera can have a resolution of 1 MP 1024 × 1024 pixels. It has been successfully used and validated in human gait analysis [ 52 , 53 , 54 ]. The RGB-D sensor system can estimate features of gait patterns in pathological individuals and differences between disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies demonstrated that Azure and the Body Tracking SDK can recognize the gait patterns and differences in individuals with disorders [ 52 , 54 , 55 , 59 ]. Azure Kinect tracking accuracy of the foot marker trajectories is significantly higher than the previous model Kinect v2 overall treadmill velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying how wearable technologies have been used over the past decade to assess gait and mobility in persons with stroke [19] Presenting an overview on the state of the art regarding the use of the different Microsoft Kinect camera models to assess gait in post-stroke individuals Describing and summarizing the main features of the available works on gait in the post-stroke population, highlighting similarities and differences in the methodological approach and primary findings [20] Reviewing the technical and clinical specifications of biofeedback systems developed for post-stroke gait rehabilitation, including the complementary use with assistive devices and/or physiotherapist-oriented cues…”
Section: Reviewmentioning
confidence: 99%
“…Alternatively, taking measurements outside the laboratory, such as with a low-cost, depth-sensing camera (e.g., Microsoft Kinect, Microsoft, USA), provides a portable and cost-effective markerless 3D motion capture device that enables depth evaluation to be integrated with typical 2D photographs [ 24 ]. In addition, the Microsoft Kinect has been suggested as a potential alternative tool with relatively high reliability and validity for clinical gait analysis [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%